Relationship between customer satisfaction with perceived quality and attitudinal loyalty / Shuqran Hafiz Supardi - Supardi, Shuqran Hafiz (2017)
Customer satisfaction was influenced by the perceived quality and affected to the loyalty. This study was aimed to determine the relationship between perceived quality of service provided and customers' satisfaction. This study was designed to determine the relationship between customers' satisfaction and attitudinal loyalty. The survey using questionnaires approach to 196 of customers at Darul Ehsan Aquatic Centre. The respondents were chosen using convenience sampling. For the purpose of this study, the questionnaire was adopted and adapted from Howat and Assaker (2013) for perceived quality and Han, Kwortnik and Wang (2008) for satisfaction and loyalty. The statistical analysis that the researcher used is Pearson correlation. The current study has indicated that, there is a significant relationship between perceived quality of service provided and customers' satisfaction (r= .729, p<.000) and there is a significant relationship between customers' satisfaction and attitudinal loyalty (r= .721, p<.000). The results obtained in this study depict, there is a significant relationship between perceived quality of service provided toward customers' satisfaction and there is a significant relationship between customers' satisfaction and attitudinal loyalty. This finding will help the facility manager to manage all of perceived quality dimension in order to attract customer to come to the centre.